2017
DOI: 10.1097/mib.0000000000000978
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity, Genetic Susceptibility, and Risk of Complications Among Individuals with Crohnʼs Disease

Abstract: Introduction Adipose tissue in mesenteric fat plays a key role in systemic and luminal inflammation. However, little is known about the role of visceral adipose tissue (VAT) and its interaction with genetic predisposition in Crohn’s disease (CD) progression. Methods Our study population included CD patients enrolled in Prospective Registry in Inflammatory Bowel Disease Study at Massachusetts General Hospital (PRISM). VAT volume was measured from CT scans using Aquarius 3D. We used logistic regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Studies in patients with CD disease using visceral adiposity as a measure of obesity have more consistently shown the increased risk of CD-related complications than those using BMI as a marker of overall obesity [58][59][60][61][62][63][64]. Erhayiem et al [58], in a study on 97 patients with CD, found that using computed tomography (CT) scanning that mesenteric fat index (MFI), defined as the ratio of areas of visceral-to-subcutaneous fat was a good marker of aggressive CD.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in patients with CD disease using visceral adiposity as a measure of obesity have more consistently shown the increased risk of CD-related complications than those using BMI as a marker of overall obesity [58][59][60][61][62][63][64]. Erhayiem et al [58], in a study on 97 patients with CD, found that using computed tomography (CT) scanning that mesenteric fat index (MFI), defined as the ratio of areas of visceral-to-subcutaneous fat was a good marker of aggressive CD.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…In another study on CD patients, CT scanning was found to be superior to BMI, and VAT volume was considered to be a useful variable and an indicator of increased risk of surgery and penetrating disease. They concluded that visceral, rather than total, adiposity may negatively influence the long-term risk of progression of CD [63].…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…Visceral adiposity is the metabolically active fraction, and could be more predictive of the risk of developing IBD that general obesity determined by the BMI. Indeed, there is evidence that obesity is able to influence not only the occurrence but also the progression of IBD; it has been shown that visceral obesity, in patients with CD, is associated with a higher probability of surgery and of penetrating disease and in ulcerative colitis with an increased risk of relapse [59]. However, in a meta-analysis regarding the evolution of IBD disease, the results showed that obese patients undergone surgery less frequently than non-obese patients (RR 0.82; 95% CI 0.72-0.93).…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Analysis of 482 prospective-registry patients with Crohn’s disease with 3D computed-tomography visceral adipose volume measurements demonstrated increased odds of surgery in the highest quintile of visceral adipose as compared to the lowest quintile (multivariable-adjusted OR 2.02; p-trend = 0.06). 160 Higher quintiles of visceral adipose volume also correlated with risk of penetrating disease (Ptrend =0.02). 160 Conversely, in a recent large, retrospective cohort study of 1494 patient with IBD, obesity was not associated with corticosteroid use, emergency department visits, hospitalizations, or surgery.…”
Section: Obesitymentioning
confidence: 97%
“…160 Higher quintiles of visceral adipose volume also correlated with risk of penetrating disease (Ptrend =0.02). 160 Conversely, in a recent large, retrospective cohort study of 1494 patient with IBD, obesity was not associated with corticosteroid use, emergency department visits, hospitalizations, or surgery. 161 There are no studies of the impact of changes in central fat or targeted weight loss therapy on disease activity in IBD.…”
Section: Obesitymentioning
confidence: 97%